Bioaccumulation characteristics of perfluoroalkyl acids (PFAAs) in coastal organisms from the west coast of South Korea. (June 2015) - Hong, Seongjin; Khim, Jong Seong; Wang, Tieyu; Naile, Jonathan E.; Park, Jinsoon; Kwon, Bong-Oh; Song, Sung Joon; Ryu, Jongseong; Codling, Garry; Jones, Paul D.; Lu, Yonglong; Giesy, John P.
Abstract: Year-round monitoring for perfluoroalkyl acids (PFAAs) along the west coast of South Korea targeting long-term changes in water and coastal organisms has been conducted since 2008. In this study, we present the most recent 5-years of accumulated data and scrutinize the relationship between concentrations in water and biota highlighting bioaccumulation characteristics. Twelve individual PFAAs in samples of water ( n  = 43) and biota ( n  = 59) were quantified by use of HPLC–MS/MS after solid phase extraction. In recent years, concentrations of PFAAs in water have been generally decreasing, but profiles of relative concentrations of individual PFAAs vary among location and year. Bioaccumulation of PFAAs in various organisms including fishes, bivalves, crabs, gastropods, shrimps, starfish, and polychaetes varied among species. However, overall bioaccumulation of PFAAs was dependent on corresponding concentrations of PFAAs in water within an area. In organ-specific distributions of PFAAs, greater concentrations of PFAAs were found in intestine of fish (green eel goby). This result suggests that PFAAs are mainly accumulated via dietary exposure, while greater concentrations were found in gill and intestine of bivalve (oyster) which suggests both waterborne and dietary exposures to these organisms. Concentrations of PFAAs in biota did not decrease over time (2008–2010), indicating that continuing bioaccumulation followed by slow degradation or excretion of PFAAs accumulated in biota. Overall, spatio-temporal distributions of PFAAs in water and bioaccumulation characteristics seemed to be associated with recent restrictions of PFOS-based products and uses of PFBS-based substitutes.